Creative Thinking Skills on the Response to Problem- Based Learning in Biochemistry Courses - M. Dwi Wiwik Ernawati; Yusnidar; Harianto; Sri Muslimatul Husna; Minarsih (Universitas Pendidikan Ganesha, 2023)
Students' creative thinking abilities are needed in higher education today, especially in biochemistry courses, by applying PBL learning. This research aimed to analyze the relationship between PBL learning and students' creative thinking abilities by applying PBL learning in biochemistry learning. The method used in this study is the mixed method using a sequential explanatory model. The sample used in this study was 52 students. The methods used in collecting data are questionnaires, interviews, and tests. The data collection instruments used in this study were essay sheets and questionnaires. Data analysis used for quantitative data is descriptive statistics and correlation tests. Qualitative data is analyzed using Miles & Huberman. The results of the research, namely from the data that has been obtained through correlation trials, show that there is a relationship between the two variables. In addition, from the interview results, the PBL learning model influences students' creative thinking skills. The data is reinforced by the results of interviews that students feel that their creative thinking skills increase with PBL learning. It was concluded that PBL learning relates to students' creative thinking abilities, especially in biochemistry courses.